A New Quararibea (Malvaceae) from the Caribbean Lowlands of Costa Rica - Cascante Marín, Alfredo (2018)
We describe and illustrate a new species of Quararibea Aubl. from Costa Rica. Quararibea reflexipetalaCascante, J. Sánchez-Gonz. & W. S. Alverson is distinguished by its pleated petals with strongly reflexed and coiled apices. Quararibea pendula W. S. Alverson also has pleated petals, which are spreading or somewhat reflexed, but its petal apices are not coiled and its flowers are borne on very long, pendulous pedicels (vs. the short pedicels of Q. reflexipetala). This new species seems to be restricted to the Río Bananito watershed of the Caribbean slopes in the eastern part of Costa Rica.